Genetic studies in coeliac disease - Turner, Graham (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2011)
This study is primarily concerned with elucidating genetic contributions to coeliac disease in the Irish population via case control based association studies. Due to the nature of complex diseases, and the large sample sizes required to successfully detect genetic factors of relatively small magnitude, as well as the need for association confirmation in independent populations, there is also a lesser focus on the role of genetic factors in the Italian, British and Dutch populations.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin